Innovative security solutions for information technology and communications : 8th International Conference, SECITC 2015, Bucharest, Romania, June 11-12, 2015. Revised selected papers /: 8th International Conference, SECITC 2015, Bucharest, Romania, June 11-12, 2015. Revised selected papers. (2015) - Unknown
No abstract available